2017
DOI: 10.1039/c7ra00295e
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of lignin: characterization and investigation of the thermal decomposition

Abstract: Lignin is an abundant polyphenol biopolymeric material chemically functionalisable to act as flame retardant in polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 39 publications
4
53
0
Order By: Relevance
“…Therefore, these changes could not be attributed to the inherent chemical or physical nature of the materials. Similar behavior was also observed in many other systems [ 5 , 7 , 37 , 38 ]. This suggests that there is a direct correlation between the heating rate and the rate of pyrolytic decomposition (and simultaneous oxidation).…”
Section: Resultssupporting
confidence: 87%
“…Therefore, these changes could not be attributed to the inherent chemical or physical nature of the materials. Similar behavior was also observed in many other systems [ 5 , 7 , 37 , 38 ]. This suggests that there is a direct correlation between the heating rate and the rate of pyrolytic decomposition (and simultaneous oxidation).…”
Section: Resultssupporting
confidence: 87%
“…For the HDO with catalysts, on the other hand, the decarboxylation reaction was more predominant than decarbonylation. Particularly for Fe 2 P/γ-Al 2 O 3 and CoMoP/γ-Al 2 O 3 catalysts, high selectivity to carbon dioxide was observed, which is likely to be attributed to promoted dehydration and decarboxylation by addition of phosphorus [21,22].…”
Section: Effect Of Reaction Conditions On Product Distributionmentioning
confidence: 97%
“…Lignin is a phenol-containing cross-linked biomacromolecule that can be isolated by two different extraction procedures (alkali and organosolv). The flame retardant efficiency of neat lignin is already known for different polymer systems [51,52,99]. Ferry et al compared the fire behavior of lignin obtained from different extraction procedures in PBS.…”
Section: Synthesis Of Phosphorus-containing Biobased Flame Retardantsmentioning
confidence: 99%
“…Ferry et al grafted phosphoros compounds onto lignin for PBS and compared it with unmodified lignin whose flame retardant properties are known in the literature [51,52]. Ferry et al compared the two neat lignins also by using cone calorimetry and reported different pHRR and TTI (time to ignition) for the alkali (102 kW/m −2 and 189 s) and organosolv (111 kW/m −2 and 25 s) lignin.…”
Section: Biobased Flame Retardants In Polyestersmentioning
confidence: 99%